The New York City tale in the urban filmography of Woody Allen - de Miguel Zamora, Marta (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Woody Allen is one of the directors who have worked the most the city on his filmography. New York City is an icon that defines his work. In order to know what the image he has projected of New York is, his urban work has been analyzed in a transversal way. The process consisted of breaking down the feature films into sequences and selecting those fragments of New York urban content. These sequences were analyzed from various perspectives: visual, oral, and narrative. The interpretation of the results leads to the conception of a coherent New York urban identity tale that goes through different stages in the director's filmography.